Incorporating Indonesian Students' "Funds of Knowledge" into Teaching Science to Sustain Their Interest in Science - A.N. Md Zain; R. Rohandi (University of Sofia, 2011)
The purpose of this study was to examine the effect of incorporating students' funds of knowledge in the teaching of science in sustaining Indonesian students' interest in science. The researchers employed mixed method approach in this study. This study took place within two suburban secondary schools in Indonesia. Two teachers and a total of 173 students (94 males and 79 females) participated in this study. The findings revealed that initially, most students expected that the teaching process would mainly include science experiments or other hands-on activities. Their preferences revealed a critical problem related to science learning: a lack of meaningful science-related activities in the classroom. The findings showed that incorporating students' funds of knowledge into science learning processes -and thus establishing students' culture as an important and valued aspect of science learning was effective in not only sustaining but also improving students' attitudes and increasing their interest in science.